Communication in the intensive care unit during COVID-19: early experience with the Nightingale Communication Method. (3rd December 2020) - Shurlock, Jonathan; Rudd, James; Jeanes, Annette; Iacovidou, Aphrodite; Creta, Antonio; Kanthasamy, Vijayabharathy; Schilling, Richard; Sullivan, Eamonn; Cooke, Joanne; Laws-Chapman, Colette; Baxter, David; Finlay, Malcolm
Abstract: Objective: To assess the utility and frequency of use of the Nightingale Communication Method, during the early operational phase of the Nightingale Hospital London (NHL) 4000-bed field hospital's intensive care unit. Design: Survey-based cross-sectional assessment. Setting: The intensive care unit at the Nightingale London hospital. Participants: Staff working in the clinical area and therefore requiring full personal protective equipment (PPE). Intervention: Survey of all staff members sampled from a single shift at the Nightingale Hospital. This investigated perceived utility and actual use of identification methods (name and role labels on visors and gowns, coloured role identification tapes) and formal hand signals as an adjunctive communication method. Main Outcome Measure: Self-reported frequency of use and perceived utility of each communication and personnel identification adjunct. Results: Fifty valid responses were received (72% response rate), covering all clinical professional groups. Prominent name/role identifications and coloured role identification tapes were very frequently used and were perceived as being highly useful. Formal hand signals were infrequently used and not perceived as being beneficial, with respondents citing use of individual hand signals only in specific circumstances. Conclusion: PPE is highly depersonalizing, and interpersonal identification aids are very useful. Despite being difficult, verbal communication is not completely prohibited, which could explain the low utility of formal hand signals. The methods developed at the Nightingale hospital have enhanced communication in the critical care, field hospital setting. There is potential for wider application to a variety of healthcare settings, in both the current situation and future pandemic scenarios.